PEMBERDAYAAN MASYARAKAT DALAM MENGURANGI RISIKO HIPERTENSI MELALUI POLA MAKAN YANG SEHAT DI DESA SUNGAI LANGKA KECAMATAN GEDONG TATAAN - Wardani, Dyah Wulan; Pramesona, Bayu Anggileo; Sutarto, Sutarto; Wahono, Endro Prasetyo (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Aisyah Pringsewu, 2024)
Life expectancy increasing in Lampung Province shows not only a prosperity increasing but also increasing in degenerative diseases including hypertension. Several studies show that aged > 55 years, having a hypertension family history, eating high diet in sodium and fat, being obese, not exercising and lack of information regarding healthy eating patterns are at greater risk of developing hypertension. This community service activity aims to empower the community to reduce the risk of hypertension by increasing knowledge about healthy eating patterns for hypertension sufferers. Activities were carried out in Sungai Langka Village, Gedong Tataan District, which included FGD and counseling. The FGD aimed to prepare information media, which continued by counseling about healthy eating patterns for hypertension sufferers. Before and after the counseling, pre and post tests are given as an evaluation. Results showed that in pre-test, 30%, 35% and 35% of participants did not understand, less understood and understood about eating patterns for hypertension sufferers, respectively. In post test, understanding increased to 50% of participants understood and 50% really understood. Based on these results, this activity can increase the knowledge of the Sungai Langka Village community regarding healthy eating patterns in reducing the risk of hypertension.